The effective CIO how to achieve outstanding success through strategic alignment, financial management, and IT governance - Brown, Eric J.; Yarberry, William A. (Auerbach Publ., 2009)
Core skills and career development -- IT governance -- IT finance -- Project management -- Creating good enough code -- Enterprise architecture -- Mergers and acquisitions -- Sourcing -- Business intelligence and analytics -- Security -- Training -- Effective use of consultants -- Operations -- Futures -- CIO interviews
Keywords: Chief information officers; Information technology / Management; Information resources management